2020
DOI: 10.1177/1758835920937902
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to immune checkpoint inhibitors in non-small cell lung cancer: biomarkers and therapeutic strategies

Abstract: The treatment landscape for patients with advanced non-small cell lung cancer has evolved greatly with the advent of immune checkpoint inhibitors. However, many patients do not derive benefit from checkpoint blockade, developing either primary or secondary resistance, highlighting a need for alternative approaches to modulate immune function. In this review, we highlight the absence of a common definition of primary and secondary resistance and summarize their frequency and clinical characteristics. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 154 publications
(222 reference statements)
1
59
0
2
Order By: Relevance
“…131 In a Chinese study, the TMB was analysed in NSCLC patients receiving anti-PD-1/PD-L1 treatment; the mPFS was significantly longer at 10.6 months in the high TMB group compared with just 3.9 months in the low TMB group (p = 0.0007), and the mOS was 21.0 months in the high TMB group and just 11.6 months in the low TMB group (p = 0.0126). 132 The circulating tumour DNA (ctDNA)-related TMB was also assessed in NSCLC patients who received anti-PD-1 or anti-PD-L1 therapy; 133 however, higher ctDNA-related TMBs were obviously related to shorter mOS and mPFS, which indicated that a higher ctDNA TMB Therapeutic Advances in Medical Oncology 13 16 journals.sagepub.com/home/tam reflected worse clinical outcomes. 134 Another group detected TMB in plasma through bloodbased cell-free DNA (cfDNA), and they were able to successfully identify NSCLC patients whose PFS was significantly improved after anti-PD-L1 therapy.…”
Section: Tmbmentioning
confidence: 99%
“…131 In a Chinese study, the TMB was analysed in NSCLC patients receiving anti-PD-1/PD-L1 treatment; the mPFS was significantly longer at 10.6 months in the high TMB group compared with just 3.9 months in the low TMB group (p = 0.0007), and the mOS was 21.0 months in the high TMB group and just 11.6 months in the low TMB group (p = 0.0126). 132 The circulating tumour DNA (ctDNA)-related TMB was also assessed in NSCLC patients who received anti-PD-1 or anti-PD-L1 therapy; 133 however, higher ctDNA-related TMBs were obviously related to shorter mOS and mPFS, which indicated that a higher ctDNA TMB Therapeutic Advances in Medical Oncology 13 16 journals.sagepub.com/home/tam reflected worse clinical outcomes. 134 Another group detected TMB in plasma through bloodbased cell-free DNA (cfDNA), and they were able to successfully identify NSCLC patients whose PFS was significantly improved after anti-PD-L1 therapy.…”
Section: Tmbmentioning
confidence: 99%
“…However, mechanisms of primary and acquired resistance largely limit the activity of these drugs, with a very low fraction of patients experiencing a prolonged response [ 89 ]. In this respect, several mechanisms of resistance to ICIs treatment have been identified and, among those associated with genetic variants of tumor cells, there are alterations of HLA , β2-microglobulin and LKB1 genes, c-Myc copy number gain, KRAS mutations, and deletions of chromosomal regions with consequent neoantigens loss [ 90 ].…”
Section: Use Of Ngs-based Cfdna Testing To Track the Acquired Resimentioning
confidence: 99%
“…In secondary resistance, patients relapse after a period of initial response as a consequence of the appearance of tumor evasion mechanisms. Primary resistance to IT accounts for 7–27% of first-line treatment and 20–44% of second-line treatment in patients with lung cancer [ 81 ]. According to the KEYNOTE-001 trial results, approximately 25% of patients treated with ICIs could develop secondary resistance [ 82 ].…”
Section: Resistance To Immune Checkpoints In Lung Cancer Immunothementioning
confidence: 99%